(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-115-128 Abstract. On the one hand the article deals with the explanation why neotraditionalism as a type of fictional thought as a feature of the Russian poetry of the 20th century can be underestimated by literature researchers, on the other hand, it serves to highlight the features of fiction world that can be used to identify a poet-neotraditionalist. Consideration the phenomenon of neotraditionalism has been impeded due to the historical circumstances influencing on the discussion of the postmodernism of modernism fate in Russia. As a result the statement on the victory of historical avant-garde, which is typical for western perception of the literature of the 20th century, has been reflected on the native literature process. Nevertheless, the key to understanding the features and peculiarities of the Russian poetic history after symbolism is connected to the acceptance of neotraditionalism as a type of fictional thought. Key words: Russian poetry, post-symbolism, neotraditionalism, poetic, fictional world